2022
DOI: 10.1152/ajpregu.00021.2022
|View full text |Cite
|
Sign up to set email alerts
|

Acral skin vasoreactivity and thermosensitivity to hand cooling following 5 days of intermittent whole body cold exposure

Abstract: We sought to examine whether short-term whole-body cold acclimation would modulate finger vasoreactivity and thermosensitivity to localized cooling. Fourteen men were equally assigned to either the experimental (CA) or the control (CON) group. The CA group was immersed to the chest in 14°C water for ≤120 min daily over a 5-day period, while the skin temperature of the right-hand fingers was clamped at ~35.5°C. The CON group was instructed to avoid any cold exposure during this period. Before and after the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(60 reference statements)
0
3
0
1
Order By: Relevance
“…This shift in skin temperature subsequently impacts various physiological indicators through neurohumoral regulation. Prior researches have demonstrated that alterations in skin temperature following cold exposure can be modulated through various strategies such as cold acclimatization or increased clothing insulation, thereby influencing bodily functions, particularly certain circulatory function indicators 17–19 . After cold exposure, cardiovascular responses can vary from different regions (forms) of cooling, which include whole‐body skin, restricted local exposure to facial skin, hands (cold pressor test), and the respiratory tract (cold air inhalation) 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift in skin temperature subsequently impacts various physiological indicators through neurohumoral regulation. Prior researches have demonstrated that alterations in skin temperature following cold exposure can be modulated through various strategies such as cold acclimatization or increased clothing insulation, thereby influencing bodily functions, particularly certain circulatory function indicators 17–19 . After cold exposure, cardiovascular responses can vary from different regions (forms) of cooling, which include whole‐body skin, restricted local exposure to facial skin, hands (cold pressor test), and the respiratory tract (cold air inhalation) 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Cold exposure generally leads to notable alterations in core temperature, primarily manifesting as a decrease in skin temperature. 15,16 This shift in skin temperature subsequently impacts various physiological [17][18][19] After cold exposure, cardiovascular responses can vary from different regions (forms) of cooling, which include whole-body skin, restricted local exposure to facial skin, hands (cold pressor test), and the respiratory tract (cold air inhalation). 20 The enhanced sympathetic nerve activity caused by decreased skin temperature during cold exposure stimulates the release of catecholamines, resulting in vasoconstriction of both peripheral and visceral arteries.…”
Section: Cardiovascular Responses After Cold Exposurementioning
confidence: 99%
“…Введение. Зимние виды спорта требуют от организма включения адаптационных механизмов реакции сердечно-сосудистой системы на периодическое действие холода Исследование [1,2] показало, что сильный холод ослабил вазореактивность пальцев к прямому локальному охлаждению Адаптация к холоду ведет к активации симпатического отдела вегетативной нервной системы, что изменяет тонус артериальных сосудов Цель исследования -выявить тонус альфа-1-адре но рецеп торов артериальных сосудов «оболочки» тела (артерии кожно-мышечной области) и артериального русла «ядра» тела (артерии тонкого кишечника) при пятидневной холодовой адаптации на восемь доз фенилэфрина Методика и организация исследования. Исследование проведено на двух группах кроликов, контрольной (N1=25) и кроликов (N2=23) после пяти дней адаптации к холоду при (t=-10' C) По реакциям доза-эффект на восемь доз фенилэфрина оценивали фармакокинетические и фармакодинамические свойства а1-адренорецепторов артерий оболочки тела и ядра тела в двойных обратных координатах Лайнувера-Берка до и после адаптации к холоду Результаты исследования и их обсуждение.…”
Section: влияние пятидневной холодовой адаптации на тонус артерий кож...unclassified
“…Research continues to try and resolve the mechanism of this response, and to assess whether it could be trained. The latter has been addressed by Keramidas and Kölegård [ 11 ]. They investigated the effect of a 5-day whole-body cold-acclimation regimen on finger vasoreactivity and thermosensitivity to local cooling, as reflected in the finger skin temperature response to hand immersion.…”
Section: Analysis and Summary Of Thematic Sessionsmentioning
confidence: 99%